RAD52 gene polymorphisms are associated with risk of colorectal cancer in a Chinese Han population - Zhang, Longyi (Medicine (Baltimore), 2017)
Upward trends in the incidence and mortality rates of colorectal cancer (CRC) in China over the past decade mean that it is critical to improve survival outcomes for patients with this malignancy. Analysis of genetic variants may identify biomarkers that have a role in CRC susceptibility and clinical outcomes in Chinese patients with CRC. RAD52 is a key mediator during DNA strand exchange and homologous recombination within mammalian cells. In this study, we explored the effects of RAD52 single nucleotide polymorphisms (SNPs) in the susceptibility and clinicopathological characteristics of Chinese Han patients with CRC. Five RAD52 SNPs (rs1051669, rs10774474, rs11571378, rs6489769, and rs7963551) were analyzed using TaqMan SNP genotyping in 281 patients with CRC and 309 healthy controls. Among those aged over 60 years in the total population, carriers of the variant C allele or at least one T allele of the rs1051669 SNP were at a lower risk of CRC than carriers of the wild-type CC variant of rs1051669, while in those carrying the rs7963551 SNP, the GT or GT+GG alleles were associated with an increased risk of CRC compared with patients carrying TT alleles. We indicated a significant correlation between RAD52 rs7963551 polymorphism and lymph node metastasis in CRC patients. In all patients, the T-T-T-T-T, C-T-T-T-T, and C-T-A-C-T haplotypes were associated with an increasing risk of CRC. Our findings suggest that 4 RAD52 SNPs (rs1051669, rs10774474, rs11571378, and rs6489769) might contribute to the prediction of CRC susceptibility. In conclusion, our study demonstrated that RAD52 polymorphisms were associated with CRC in a Chinese Han cohort.